Experimental and theoretical investigations of functionalized boron nitride as electrode materials for Li-ion batteries. Issue 33 (16th March 2016) - Zhang, Fan; Németh, Károly; Bareño, Javier; Dogan, Fulya; Bloom, Ira D.; Shaw, Leon L.
Abstract : The feasibility of synthesizing functionalized h-BN (FBN) via the reaction between molten LiOH and solid h-BN is studied for the first time and its first ever application as an electrode material in Li-ion batteries is evaluated. Abstract : The feasibility of synthesizing functionalized h-BN (FBN) via the reaction between molten LiOH and solid h-BN is studied for the first time and its first ever application as an electrode material in Li-ion batteries is evaluated. Density functional theory (DFT) calculations are performed to provide mechanistic understanding of the possible electrochemical reactions derived from the FBN. Various materials characterizations reveal that the melt-solid reaction can lead to exfoliation and functionalization of h-BN simultaneously, while electrochemical analysis proves that the FBN can reversibly store charges through surface redox reactions with good cycle stability and coulombic efficiency. DFT calculations have provided physical insights into the observed electrochemical properties derived from the FBN.